A Comparison of the Hot Deformation Behavior and Constitutive Model of the GH4079 Alloy - Weifeng Ying; Jia Hou; Shengnan Jiang; Jianan Wang (Crystals)
In this paper, GH4079 alloy was thermally compressed under processing conditions of 1025 °C–1200 °C and 0.001 s−1–1 s−1. This article established the strain compensation Arrhenius constitutive equation, the improved Johnson–Cook constitutive equation, and the strain compensation Arrhenius constitutive model based on phase transition temperature segmentation and calculated the correlation coefficient (R) and local relative error (AARE) to verify the accuracy of the model, respectively. Finally, a certain microstructural analysis was combined. It can be concluded that the rheological stress of alloy GH4079 gradually decreases with the increase in temperature and strain rate. The AARE values of these three models are 21.09%, 20.47%, and 10.62%, respectively. The strain compensation Arrhenius model based on phase transition temperature segments can better describe the thermal deformation behavior of GH4079. By integrating this model, appropriate processing conditions can be selected to regulate the microstructural organization and achieve optimization during the practical application of the alloy.